When two worlds collide: acute HIV in the shadow of DADA2 deficiency - Zainulabid, Ummu Afeera; Cheong, Xiong Khee; Kori, Najma; Othman, Siti Norlia; Nawawi, Mohammad Ismim Putera; Ali, Adli; Periyasamy, Petrick (Elsevier Ltd, 2025)
Deficiency of adenosine deaminase 2 (DADA2) is a rare autoinflammatory and immunodeficiency disorder characterized by systemic inflammation, recurrent fever, vasculopathy, and immunological abnormalities. Its clinical features can overlap with those of acute viral infections, posing significant diagnostic challenges. Acute HIV infection is frequently associated with a febrile viral syndrome, which can mimic the symptoms and disease progression of DADA2. Here, we report a case of acute HIV infection in an adolescent with underlying DADA2, highlighting the diagnostic complexity due to overlapping clinical features.